2005
DOI: 10.1007/s10439-005-3310-9
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Hemodynamic Forces in Vascular Cell Differentiation

Abstract: The pulsatile nature of blood flow is a key stimulus for the modulation of vascular cell differentiation. Within the vascular media, physiologic stress is manifested as cyclic strain, while in the lumen, cells are subjected to shear stress. These two respective biomechanical forces influence the phenotype and degree of differentiation or proliferation of smooth muscle cells and endothelial cells within the human vasculature. Elucidation of the effect of these mechanical forces on cellular differentiation has l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(57 citation statements)
references
References 61 publications
(94 reference statements)
3
54
0
Order By: Relevance
“…Hemodynamic forces, shear stress, and stretch-induced Ca 2ϩ signals are a major determinant of vascular cell morphology and function (12,34). However the gating mechanisms and the mechanical sensors that mediate the response to hemodynamic force have not been clarified.…”
Section: Resultsmentioning
confidence: 99%
“…Hemodynamic forces, shear stress, and stretch-induced Ca 2ϩ signals are a major determinant of vascular cell morphology and function (12,34). However the gating mechanisms and the mechanical sensors that mediate the response to hemodynamic force have not been clarified.…”
Section: Resultsmentioning
confidence: 99%
“…It has been postulated that shear stress, the tangential force exerted by the flowing blood on the vascular endothelial lining, is of prime importance in determining endothelial phenotype. 4,5 Over recent years, the zinc finger transcription factor lung Krüppel-like factor (LKLF/KLF2) has emerged as a prime and pivotal candidate for directly relaying biomechanical shear forces into a gene transcription profile that might determine endothelial phenotype in response to flow. [6][7][8][9][10] We previously demonstrated that KLF2 mRNA and protein levels are substantially and uniquely induced by prolonged steady or pulsatile laminar flow both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in PDGF-BB -/-mice, SMCs are not recruited around vessels, and pericytes are aberrantly located (13). Beyond cytokines, mechanical forces contribute to SMC development and postnatal maturation, as cyclical strain results in upregulation of contractile proteins within SMCs along with increases in ECM secretion (14).…”
Section: Introductionmentioning
confidence: 99%